Patent Development Strategy through PCT (Patent Cooperation Treaty) International Registration System: Challenge for Intellectual Property (IP) Attorneys in Indonesia - Suyud Margono (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research addresses the role of Intellectual Property (IP) Lawyers in patent registration and prosecution, particularly in the Patent Cooperation Treaty (PCT) context. In a complex research and development environment, an understanding of the risk of patent imitation is essential. This study aims to analyze the strategy of international patent registration through the PCT system and evaluate its effectiveness compared to national patent registration in Indonesia. This research uses a normative legal approach by analyzing the literature and practical aspects relating to international patent registration through the PCT system. The research findings show that Intellectual Property Lawyers need to have in-depth knowledge of the national and international patent registration systems. The research also highlights the challenges for inventors with limited budgets in choosing between national Patent and PCT registration, as well as the importance of strategic planning in registration to protect innovation. This research underscores the important role of IP Attorneys in assisting inventors through the patent registration process, both nationally and internationally, and emphasizes that the PCT system is a viable option to effectively protect innovation while managing costs.